Proper and improper separability - Timpson, C; Brown, H (World Scientific, 2005)
The distinction between proper and improper mixtures is a staple of the discussion of foundational questions in quantum mechanics. Here we note an analogous distinction in the context of the theory of entanglement. The terminology of "proper" versus "improper" separability is proposed to mark the distinction.